PENGARUH MEDIA LAGU BERBAHASA INGGRIS TERHADAP PENGUASAAN KOSAKATA SISWA SEKOLAH DASAR - Dhea Shalsabila; Siti Halidjah (STKIP Subang, 2026)
Vocabulary mastery is a fundamental aspect of English language learning for elementary school students. However, the limited use of interactive teaching methods often poses a challenge in improving their language skills. This study aims to analyze the effectiveness of using English songs in improving elementary school students’ vocabulary mastery. Using a literature review method, this study examines various academic sources regarding the benefits of songs in language learning, particularly in terms of improving vocabulary comprehension and retention. The results indicate that using songs as a learning medium can boost student motivation, enrich vocabulary, and facilitate English comprehension and pronunciation in a more enjoyable way. Songs have also proven effective in increasing student engagement in the learning process, compared to conventional methods. Thus, the use of songs in English language learning is recommended as an innovative strategy to improve students’ vocabulary mastery more effectively and interactively.